2018
DOI: 10.2319/021018-115.1
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic management of a dental anomaly pattern (DAP) including mandibular canine transmigration: A case report: A challenging treatment but worth it!

Abstract: Orthodontic technology has advanced to the point where management of cases with multiple dental anomalies should be within an orthodontist's daily armamentarium. A patient with bilateral agenesis of lower second premolars, delayed development, and transmigration of a mandibular canine was treated with the aid of hemisection, indirect/closed exposure, application of continuous force, targeted delivery, and strict attention to keeping the roots as much in bone as possible. This was accomplished without implants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 23 publications
(25 reference statements)
1
19
1
Order By: Relevance
“…articles of the 18 full-text articles retrieved (Agarwal et al, 2013;Cavuoti et al, 2016;Jaisinghani et al, 2019;Janakiraman et al, 2016;Koszowskiet al, 2015;Kuftinec et al, 1995;Kulkarni, & Lee, 2016;Northway, 2019;Peerlings, 2010;Plaza, 2016;Shukla et al, 2019;Sinko et al, 2016;Üçüncüet al, 2011;Umashree et al, 2013;Vaidaet al, 2014;Vera-Guerraet al, 2019;Verma et al, 2012;Wertz, 1994) were excluded because of the following: in three articles, the treatment included the extraction of the canine (Janakiraman et al, 2016;Kuftinec et al, 1995;Umashree et al, 2013), two articles were related to the autotransplantation approach (Kulkarni, & Lee, 2016;Verma et al, 2012), and one study focused on a non-transmigrated canine (Agarwal et al, 2013). Apart from case reports and cohort studies, no other design was found during the search.…”
Section: Search Strategy and Eligibility Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…articles of the 18 full-text articles retrieved (Agarwal et al, 2013;Cavuoti et al, 2016;Jaisinghani et al, 2019;Janakiraman et al, 2016;Koszowskiet al, 2015;Kuftinec et al, 1995;Kulkarni, & Lee, 2016;Northway, 2019;Peerlings, 2010;Plaza, 2016;Shukla et al, 2019;Sinko et al, 2016;Üçüncüet al, 2011;Umashree et al, 2013;Vaidaet al, 2014;Vera-Guerraet al, 2019;Verma et al, 2012;Wertz, 1994) were excluded because of the following: in three articles, the treatment included the extraction of the canine (Janakiraman et al, 2016;Kuftinec et al, 1995;Umashree et al, 2013), two articles were related to the autotransplantation approach (Kulkarni, & Lee, 2016;Verma et al, 2012), and one study focused on a non-transmigrated canine (Agarwal et al, 2013). Apart from case reports and cohort studies, no other design was found during the search.…”
Section: Search Strategy and Eligibility Criteriamentioning
confidence: 99%
“…Apart from case reports and cohort studies, no other design was found during the search. After the exclusion criteria had been met, 12 full-text articles (Cavuoti et al, 2016;Jaisinghani et al, 2019;Koszowski et al, 2015;Northway, 2019;Peerlings, 2010;Plaza, 2016;Shukla et al, 2019;Sinko et al, 2016;Üçüncü et al, 2011;Vaida et al, 2014;Vera-Guerra et al, 2019;Wertz, 1994) remained to be retrieved and examined for further evaluation. The characteristics of the included studies are summarized in Figure 1, and the key findings about the orthodontic biomechanics and clinical considerations were collected and are summarized in Tables 3 and 4.…”
Section: Search Strategy and Eligibility Criteriamentioning
confidence: 99%
See 3 more Smart Citations